The relationship between sustainable nutrition and healthy food choice: a cross-sectional study - Arslan, Nurgül; Alataş, Hacer (The European Research Journal, 2023)
Objectives: The aim of this study was to evaluate university students' attitudes toward sustainable nutrition, their level of knowledge in this area, and the associations between these variables and food preferences. Methods: This study was conducted with university students between the ages of 19-45. The study data were collected between May 2022 and July. In the study, the Scale of sustainable nutrition knowledge was used for the sustainable nutrition knowledge level of individuals. The food choice scale was used to determine the food preference and the Sustainable and Healthy Eating Behaviors scale was used to determine the health food choice preference. Results: The study involved 467 participants, and female made up 64.67% of the study's participants. The mean age of the group was 23.21 ± 6.13 years. Knowledge of sustainable nutrition increases by 1.365 for every 0.821 increase in educational level. The sustainable nutrition knowledge score increased by 1.529 points, the scale score for sustainable and healthy eating behaviors increased by 0.651 points, and the monthly income to the model increased by 1.611 times for every 1.109 unit (p = 0.005). Conclusions: Our survey shows that most college students believe eating sustainably is important. As people's education and knowledge about sustainable nutrition rise, so do their healthy eating habits. Expand sustainable nutrition education, add it to the curriculum, and create nutrition guides to promote this novel concept in our country.